The Ecologic Products and the Importance of their Consumption for the Human Health - Corina Constanța Sîrbu; Tiberiu Iancu; Ioan Brad; Tabita Adamov; Elena Peț; Genoveva Buzamăt; Diana Marin; Claudia Sîrbulescu (Scientific Papers Animal Science and Biotechnologies, 2023)
This study intends to analyze the perception of young people regarding the ecologic products, their consumption and implicitly the awareness of their effect on the human health. The geographic area where we realized the study was Timisoara by distributing a questionnaire in different places: universities, super-markets, mall. After analyzing the results, we noticed that 80% of the young people consider that the food is very important for a healthy life. The majority of the young people questioned, even knowing the characteristics of the bio products, consumed fruits and vegetables bought from stores specialized in ecologic products. From our study, we can say that the young people are interested in the ecologic products sold in Timisoara and they are aware about their impact on the human health.